Adoption of spice crops technological interventions in arid Rajasthan - Sharma, K.C.; Ram, Hanuman; Singh, H.P. (Annals of Agricultural Research, 2016)
This study was conducted in Jodhpur (Rajasthan) in the year 2010 to know the extent of adoption ofrespondents regarding different technological interventions of spice crops. A sample of 160respondents was taken from IVLP operated (Beneficiary) and non-operated (Non-beneficiary)villages. Further, the extent of adoption of package of practices of spice crops was measured by aquestionnaire and then MPS was calculated, ranks were assigned and Correlation in ranks was alsodetermined. The findings revealed that more number of beneficiary respondents fall in high adoptiongroup as compared to non-beneficiary. There was significant correlation between the ranks givento adoption of various package of practices of spice crops production technology by the beneficiariesand non-beneficiar respondents. There was significant difference in the extent of adoption alsobetween both the respondents.